Relation of American literature to American nationality - Houghman, Sarah C. (My University, 1903)
Introduction: America's total contribution to the world's literature when compared with that of many other nations, is both inferior in quality, and insignificant in amount. If American literature should claim our attention through its intrinsic literary value only, the proportion of time which it justly demand from us would be much smaller than it is. It is not, therefore, simply for the purpose of becoming acquainted with particular authors that we now take up the study of American literature; it is rather for the purpose of studying the relation which that literature bears to our national life. American literature does not mean merely the literature of the United States, produced since the adoption of the Constitution; it is far older than our national life. In its origin, it was not the voice of a united people and independent nation, but the disconnected and stammering utterances of a straggling line of English colonies, fighting for a foothold along the coast of an inhospitable land. Of course, the literature is now and has been for more than a century, the product of a politically independent nation. Our intellectual dependence upon England has likewise gradually lessened, and for more than a century we have been moving toward self confidence and independence in literary methods and thought. Our literature made its first feeble beginnings in a most fortunate time, when, as says Tyler: "The firmament of English literature was all ablaze with the light of her full orbed and most dazzling writers, the wits, the dramatists, scholars, orators, singers, philosophers, who formed that incomparable group of men gathered in London during the earlier years of the seventeenth century."
Citation: Houghman, Sarah C. Relation of American literature to American nationality. Senior thesis, Kansas State Agricultural College, 1903.
Morse Department of Special Collections
Keywords: English Literature; English; American Literature; Theses